Formulation of eucalyptus oil-zinc sulfide hybrid nanoemulsion and evaluation of its larvicidal potential against Aedes aegypti - Kaur, Komalpreet; Vashishat, Nisha; Kaur Kocher, Devinder (African Entomology, 2023)
The growing threat of vector- borne diseases and environmental pollution has prompted the nanotechnology based investigations. The present study aimed to use one of the nanotechnological applications with larvicidal potential against Aedes aegypti by preparing aqueous hybrid nanoemulsion of zinc sulfide nanoparticles and Eucalyptus globulus oil. The mean droplet size of prepared and most stable hybrid nanoemulsion (9.5 ppm) was found to be 60±10.00 nm with rectangular shape. The hybrid nanoemulsion exhibited LC50 and LC90 values of 7.63 and 9.22 ppm respectively against larval stages of Aedes aegypti. The findings obtained from the larvicidal assay were corroborated with SEM, histological and biochemical profiles of Aedes larvae after treating with hybrid nanoemulsion. Under simulated conditions, nanohybrid treatment demonstrated optimum larvicidal potency after 48 hrs of exposure. Further, biosaftey studies of hybrid nanoemulsion were carried out against Scapholebris kingi and this larvicidal concentration of nanohybrid was found to be non-toxic to this species. Thus, the following research explains the larvicidal efficacy of zinc sulfide based hybrid nanoemulsion of eucalyptus oil formulated during the present study is a step towards safe and efficient approach against dengue spreading vector mosquito, Aedes aegypti.